Education Service for Children of Unregistered Indonesian Migrant Workers in Malaysia - Maharani, Deaningma; Mahardhani, Ardhana Januar; Cahyono, Hadi; Fadilah, Afifah Nur (Jurnal Borneo Administrator, 2024)
Following registration records for the 2022 Unlicensed Foreign Worker Recalibration Program (PATI), 418,649 Indonesian citizens are participating in the labour recalibration program in Malaysia, so this will have a negative impact, namely an increase in the number of children of Indonesian migrant workers. Malaysian immigration authorities do not allow all migrant workers to invite their families to come live in Malaysia. This causes migrant workers' children to feel ostracized, discriminated against and denied their right to education due to a lack of access to education and love from their parents. The research aims to explore the role of government in providing educational services. The research method is descriptive and qualitative. The subjects of this research were the Indonesian and Malaysian governments, the children of unregistered immigrant workers in several guidance studios, and migrant workers. Data was collected through interviews, observation, and documentation. Data analysis techniques include data reduction, data presentation, and conclusion drawing. The research results found that the rights of Indonesian citizens and children have been fulfilled, such as access to education. Fulfilling these needs is achieved through the role of government, such as establishing formal and non-formal schools to foster a sense of comfort and protection. In addition, the government, with its role, can create appropriate policies to provide rights and safety to the children of unregistered immigrant workers